Antimicrobial polymers: elucidating the role of functional groups on antimicrobial activity - Ihtisham Ul Haq; Rafael Pinto Vieira; William Gustavo Lima; Maria Elena de Lima; Katarzyna Krukiewicz (Arab Journal of Basic and Applied Sciences)
The swift increase in antimicrobial resistance across the world presents a significant challenge, further raised by insufficient advancement in the design of new antimicrobial agents. Over the past two decades, a variety of sources has been investigated for generating new antimicrobials. Recently, antimicrobial polymers (APs) have emerged as multifaceted agents, displaying effectiveness against a range of pathogens such as bacteria, fungi, and viruses. Their notable biocompatibility, efficiency, multifunctionality, and ease of modification make them a focal point of antimicrobial research. APs are particularly valued for their structural versatility, which allows for the integration of antimicrobial functional groups. Polymer functionalization does not only enhance or introduce antimicrobial properties but also maintains high levels of biocompatibility. This review reveals broad antimicrobial breadth of APs, which can be potentially used in antiseptics, food packaging, and in biomedical sector, as e.g. medical implants’ coatings. In laboratory settings, APs have shown promising therapeutic effects, however there remains an urgent need for computational biology to fully understand their antimicrobial behaviour and stability. Recombinant biotechnological approaches are essential for facilitating the production of APs and require industrial collaboration to effectively optimize and scale up these production processes.